Evaluation of a DVD-based self-help program in highly socially anxious individuals - pilot study - Mall, Anna Katharina; Mehl, Annette; Kiko, Sonja; Kleindienst, Nikolaus; Salize, Hans Joachim; Hermann, Christiane; Hoffmann, Torsten; Bohus, Martin; Steil, Regina (Behavior therapy, 2011)
High social anxiety is a risk factor for the incidence of social anxiety disorder (SAD). Early diagnosis and intervention may prevent more severe psychiatric courses. Self-help programs may be a convenient, accessible, and effective intervention. This study examined the efficacy of a newly developed self-help program for SAD in individuals with subthreshold social anxiety. A total of 24 highly socially anxious individuals were randomly assigned to a DVD-based self-help program or to a wait-list control group. The self-help program is based on the cognitive model according to Clark and Wells (1995; adapted to German by Stangier, Clark, & Ehlers, 2006) and comprises eight sessions. ANOVAs based on an intention-to-treat model were used for data analyses. The self-help program was well accepted; just one person withdrew during the intervention. There were significant Time× Group interactions on all primary outcome measures. For the intervention group moderate to high within-groups effect sizes up to Cohen's d=1.05 were obtained. Between-groups effect sizes ranged from 0.24 to 0.65 in favor of the active intervention. The newly developed DVD-based self-help program seems to be a promising intervention for highly socially anxious individuals as it reduces social anxiety symptoms.
Gesehen am 09.08.2022